2008
DOI: 10.1097/gme.0b013e3181728467
|View full text |Cite
|
Sign up to set email alerts
|

Implications of diminished ovarian reserve (DOR) extend well beyond reproductive concerns

Abstract: Our data suggest that DOR unmasked in the context of infertility evaluation has adverse implications for a woman's well-being that extend well beyond the thus far appreciated reproductive concerns. A decline in ovarian hormones, specifically estrogen and testosterone, concomitant with DOR may be hypothesized as a mechanism that can explain the observed multisystem ramifications of DOR including increased bone turnover, low BMD, sexual distress, and disturbed sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…Sleep disturbances are thought to be common in women undergoing infertility treatment [36] despite minimal data to support this hypothesis [69,70,84]. In one investigation evaluating a heterogeneous group of women in infertility clinic, 34 % answered yes to the question Bdo you experience disturbed sleep^ [84].…”
Section: Sleep Disturbances In Women Undergoing Infertility Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbances are thought to be common in women undergoing infertility treatment [36] despite minimal data to support this hypothesis [69,70,84]. In one investigation evaluating a heterogeneous group of women in infertility clinic, 34 % answered yes to the question Bdo you experience disturbed sleep^ [84].…”
Section: Sleep Disturbances In Women Undergoing Infertility Treatmentmentioning
confidence: 99%
“…In one investigation evaluating a heterogeneous group of women in infertility clinic, 34 % answered yes to the question Bdo you experience disturbed sleep^ [84]. Analysis with multivariable logistic regression (adjusting for race, BMI, and vasomotor symptoms) found that among premenopausal infertile women, those with diminished ovarian reserve were 20 times more likely to experience disturbed sleep.…”
Section: Sleep Disturbances In Women Undergoing Infertility Treatmentmentioning
confidence: 99%
“…In addition to the rather dismal implications of diminished ovarian reserve (DOR) from the perspective of success of fertility treatments, limited data suggest that premenopausal women manifesting features of DOR may be destined for an early menopause (5-7). Equally concerning are suggestions that processes contributory to morbidities of postmenopausal years, specifically skeletal fragility and risk for cardiovascular disease, may be initiated concomitantly with decline in ovarian reserve (8,9), thus adding to the psychological burden (10) and potential health care-related cost attributable to premature decline in ovarian reserve.Quantitative and qualitative decline in the oocyte repertoire and a concomitant impaired granulosa cell (GC) efficiency are described in the context of DOR (11-13) and are suggested as contributors to the magnitude of subfertility in these women. Lower E 2 levels during attempts at ovarian hyperstimulation are well described, as is evidence of luteal dysfunction in association with DOR (3).…”
mentioning
confidence: 97%
“…High levels of psychological stress, anxiety, insomnia, depression, and sexual function changes have been reported during in vitro fertilization-embryo transfer (IVF-ET) [1][2][3][4][5][6]. These are related to a number of stresses that are the results of both the diagnosis and treatment of infertility [7].…”
mentioning
confidence: 99%